Role of Aristotelian Virtue Ethics towards Environmental Protection - Anita Jena; Sarita Kar (International Journal of Advanced Science and Technology, 2020)
The environmental problems such as deforestation, climate change, ozone layer depletion, greenhouse effect and pollution of air, water and soil are the most challenging phase that arises around the world (Singh, 2009, 40). These are the consequences of unethical behavior of human beings. Human is the most powerful living being on the earth and they have misused their physical and mental power to satisfy their greed rather than need, which has resulted in degradation of the natural environment. They have maltreated the nature and exploited it for their economic benefit which gave them a mastery over it (Chopra, 2016, 1594). Moreover, the environmental degradation and human moral deterioration are interlinked and we need a kind of moral revolution to transform human behavior for the welfare of the society with special reference to the Aristotelian Virtue Ethics rather than Consequentialist and Deontology ethics. Aristotelian Virtue ethics is primarily concerned with what kind of people we should be, what kind of characters we should have, and how we should act (Banks, 2012). This directly leads to develop one’s character and pro-environmental attitudes to wisely use the natural resources; more specifically, preserve the natural environment which ensures the environmental sustainability.